2020
DOI: 10.1109/tmtt.2020.3011004
|View full text |Cite
|
Sign up to set email alerts
|

Glide-Symmetric Metallic Structures With Elliptical Holes for Lens Compression

Abstract: In this paper, we study the wave propagation in a metallic parallel-plate structure with glide-symmetric elliptical holes. To perform this study, we derived a mode-matching technique based on the generalized Floquet theorem for glidesymmetric structures. This mode-matching technique benefits from a lower computational cost since it takes advantage of the glide symmetry in the structure. It also provides physical insight on the specific properties of Floquet modes propagating in these specific structures. With … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…With these graphs, it is demonstrated that glide symmetry produces more stable elliptical contour lines for a larger range of frequencies. Additionally, as demonstrated in [17], [52], glide symmetry is able to produce higher refractive indices than conventional unit cells. This is beneficial, for example, for compressing the size of lenses with transformation optics, or for creating optical illusions.…”
Section: Anisotropymentioning
confidence: 98%
See 3 more Smart Citations
“…With these graphs, it is demonstrated that glide symmetry produces more stable elliptical contour lines for a larger range of frequencies. Additionally, as demonstrated in [17], [52], glide symmetry is able to produce higher refractive indices than conventional unit cells. This is beneficial, for example, for compressing the size of lenses with transformation optics, or for creating optical illusions.…”
Section: Anisotropymentioning
confidence: 98%
“…More recently, it has been demonstrated that glide symmetry can also be employed to increase the level of anisotropy (on-axis) of periodic structures. In particular, this concept was demonstrated for rectangular [19] and elliptical holes [52] in a parallel plate, and in dielectric slabs with holey cladding on top and bottom [17].…”
Section: Anisotropymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been demonstrated that glide-symmetric structures are less dispersive [12,13] and can provide a higher effective refractive index [13][14][15][16], effective permeability [17], and level of anisotropy [18], compared to their non-glide counterparts. These properties have been used to design planar lenses in [13,[19][20][21][22]. Furthermore, while the stop-band between the first two modes is suppressed in glide-symmetric structures, a large stop-band exists at higher frequency [23][24][25].…”
Section: Introductionmentioning
confidence: 99%